Design Of Dynamic System Simulation Model Of Trash Bin Production Process at Harapan Mulya Putri Company - Yojana, Ratna Mira Yojana; Saputra, Surya Saputra; Astuti, Pudji Astuti (JURNAL TEKNIK INDUSTRI, 2024)
Harapan Mulya Putri is a manufacturing company established in 2010. This company produces equipment for cleaning or cleaning tools, hotel equipment, restaurant equipment, household equipment, and traffic signs. Problems encountered by Harapan Mulya Putri company that the number of stainless steel trash backorders will reach 28% in 3 months. This study aims to reduce the number of back orders in the production process of stainless steel trash bins. Reducing the number of back orders is done by designing a simulation model of stainless steel trash bin production. The method used is a dynamic system simulation. Three scenarios are used to maximize the fulfillment of consumer demand. The first scenario is a policy of adding raw materials suppliers send, such as 150 units of stainless steel plates. The simulation results for the first scenario resulted in a 75% decrease in back orders. The second scenario is ordering based on the bill of material grouping to optimize raw material utilization. The simulation results of the second scenario reduced back orders by 56.25%. The third policy scenario is combined with the first and second scenarios. The results of the third simulation show that back orders have decreased by 87.5%. Thus, the selected scenario is the third scenario.